2014
DOI: 10.1134/s1022795414120059
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphic variants of FTO and MC4R genes with obesity in a Tatar population

Abstract: Obesity is a chronic relapsing disease that leads to numerous ailments and requires lifelong treat ment. Genetic predisposition is one of the mostly discussed aspects of obesity development, and genome wide association studies have provided evidence that several variants of the FTO and MC4R genes are signif icantly associated with obesity. In this study the association of FTO (rs9939609, rs7202116, and rs9930506) and MC4R (rs12970134 and rs17782313) genes' SNPs with obesity in Tatar women has been analyzed. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…In several populations, the MAF of MC4R rs17782313 varies from 24 % to 26 %; Therefore, the MAF of MC4R rs17782313 in Koreans (25 %) was comparable to studies in other ethnicities [ 11 , 14 , 16 ]. Those previous studies found that the MC4R rs17782313 C allele was a risk allele for obesity.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In several populations, the MAF of MC4R rs17782313 varies from 24 % to 26 %; Therefore, the MAF of MC4R rs17782313 in Koreans (25 %) was comparable to studies in other ethnicities [ 11 , 14 , 16 ]. Those previous studies found that the MC4R rs17782313 C allele was a risk allele for obesity.…”
Section: Discussionsupporting
confidence: 71%
“…Those previous studies found that the MC4R rs17782313 C allele was a risk allele for obesity. The MC4R rs17782313 CC genotype has a strong positive association with BMI which has been clearly demonstrated in European and Tatar populations in which subjects with the rs17782313 variant had higher BMIs [ 11 , 14 ]. These results suggest that the MC4R minor allele is a risk factor for obesity across ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of the same population revealed association between the MC4R C allele and food energy intake, which was regarded as a factor directly related to an elevated risk of obesity [ 49 ]. Higher BMI scores were observed in Chinese people and Tatar women, regardless of whether they were homo- or heterozygotes of the C allele of the MC4R rs17782313 polymorphism (unlike carriers of the T allele) [ 50 , 51 ]. The study of Guan et al did not provide evidence for the relationships between NAFLD and the tested gene polymorphisms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%